A Role for MicroRNA-155 Expression in Microenvironment Associated to HPV-Induced Carcinogenesis in K14-HPV16 Transgenic Mice - Isabel Paiva (2015)
Human Papillomavirus cause a number of diseases most notably cervical cancer. K14-HPV16 transgenic mice expressing the HPV16 early genes in squamous epithelial cells provide a suitable experimental model for studying these diseases. MicroRNAs are small non-coding RNAs that play an important role in regulating gene expression and have been suggested to play an important role in cancer development. The role of miR-155 in cancer remains controversial and there is limited evidence linking this miRNA to HPV-associated diseases. We hypothesized that miR-155 expression modulates each tissue's susceptibility to develop HPV-associated carcinogenesis. In this study, we analyzed miR-155 expression in ear and chest skin samples from 22-26 weeks old, female K14-HPV16 transgenic (HPV16+/-) and wild-type (HPV-/-) mice. Among wild-type mice the expression of miR-155 was lower in ear skin compared with chest skin (p = 0.028). In transgenic animals, in situ carcinoma was present in all ear samples whereas chest tissues only showed epidermal hyperplasia. Furthermore, in hyperplastic chest skin samples, miR-155 expression was lower than in normal chest skin (p = 0,026). These results suggest that miR-155 expression may modulate the microenvironmental susceptibility to cancer development and that high miR155 levels may be protective against the carcinogenesis induced by HPV16.